DIFFICULTIES FOR DENTAL SURGEONS REGARDING THE EARLY DIAGNOSIS OF MOUTH CANCER IN PRIMARY HEALTH CARE: LITERATURE REVIEW - Rui Callou Filho, Cesario; Valrilania de Oliveira Rodrigues, Antônia; César Teixeira Da Silva Araújo, Carlos; Vitória De Assis Paula, Emilly; Miranda De Souza Abreu, Samuel (Health and Society, 2024)
Introduction: In Brazil, oral cancer disease is considered a malignant neoplasm of the lip, tongue, gums, floor of the mouth, hard palate and other parts of the mouth. It represents a serious public health problem due to the high rates of late diagnoses and, consequently, the significant rates of morbidity and mortality. General objective: This is a research developed through an opinion article focusing on the dental surgeon’s approach to diagnosis in Primary Health Care (PHC). Methods: This is an opinion article survey, developed from February to June 2024, through the reflection of the texts published in the area as well as through the guidelines of the dental surgeon in PHC. Results: In the end, it can be seen that associated factors evidence this difficulty, such as the lack of materials for biopsy performance. Another important point is the non-implementation of family health strategies as an approach to the prevention of oral cancer. Final considerations: It can be stated that the training of professionals is an important factor for early diagnosis, as well as the expansion of resources.